PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE QUESTION STUDENT HAVE BERBANTUAN MEDIA GAMBAR TUNGGAL DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN DURI SANGGE - Hardayanti, Indira; Supriadi; Nurdiansyah, Erwin; Mulyadi; Jumrah, Abrina Maulidnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to: (1) describe the implementation of the Question Student Have (QSH) cooperative learning model assisted by single-image media in science and social studies (IPAS) learning for fifth-grade students at SDN Duri Sangge; and (2) determine the improvement in students' IPAS learning outcomes after the implementation of the learning model. This study employed Classroom Action Research (CAR), conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. The participants were all 28 fifth-grade students of SDN Duri Sangge. The research instruments included observation sheets for teacher and student activities, learning achievement tests, and documentation. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive qualitative analysis for teacher and student activities, while students' learning outcomes were analyzed using descriptive quantitative analysis based on the percentage of learning mastery with a Minimum Learning Achievement Criterion (KKTP) of 75. The results indicated that the implementation of the Question Student Have (QSH) cooperative learning model assisted by single-image media improved the quality of the IPAS learning process. Teacher activity increased from 77% in Cycle I to 97.77% in Cycle II, while student activity improved from 64% to 98.33%. Furthermore, students' learning outcomes showed a significant improvement, as reflected in the increase in the average score from 75.54 in Cycle I to 90.36 in Cycle II, with the percentage of learning mastery rising from 67.86% to 100%. Therefore, the Question Student Have (QSH) cooperative learning model assisted by single-image media is effective in improving both student participation and learning outcomes in IPAS at the elementary school level.